Migration Governance and Border Security in Northeast Nigeria - Ogbue, Sylvia Chinaza; Okafor, Celestine Ogechukwu; Ngoka, Ruth Obioma (Journal of Contemporary International Relations and Diplomacy, 2025)
Migration governance and border security are critical aspects of national security. Migration is a dynamic feature of population distribution and has the potential to jeopardize national security if not well-managed. Nigeria's security is threatened by transnational organized crimes, including irregular migration and the proliferation of Small Arms and Light Weapons (SALW) due to the nature of the country's boundary contingency. There is a dearth of a multi-layered approach that includes surveillance technology, personnel, and infrastructure to handle border security challenges in Nigeria. This study analyzes the relationship between migration governance and border security in Nigeria. The study adopted Everett Lee’s theory of migration, while relying on documentary method for data collection and were analysed qualitatively. The study argued that irregular migration sustained by an expansive border, a lack of manpower, and corruption undermined border security in Northeast Nigeria. Weak enforcement of trans-border agreements, limited cooperation between Nigerian security forces and law enforcement officers in neighboring states, and poor border security funding accounted for the rise in the proliferation of SALW in Northeast Nigeria. To regulate irregular migration into the Northeast, Nigerian government should provide adequate manpower, training, incentives, and equipment for the grooming of efficient and uncompromising border security agencies.